Island Girl, Universal Woman: Peig: A Scéal Féin (1998) as Narrative of Class, Labour and Femininity - SORCHA SINÉAD DE BRÚN (Open Library of Humanities, 2024)
This article reappraises the Irish-language autobiography, Peig, as a unique account of the experience of life and work by a woman of the rural Irish speaking subsistence class. Peig is a seminal Irish language text, both as a depiction of class and gender-based conflict, and as an Irish language work that describes intersectional issues of justice, labour, rights and femininity from childhood to old age. I examine the narrative through the lenses of home, poverty, housing, work, marriage, children, friends, foes and loss. Peig depicts great resilience in the face of structural inequalities and localised injustice. The sustaining nature of intergenerational female friendships plays the central role in Peig’s account of her life. Arguing that the text belongs to the shared histories of women across the world, from China to the Middle East and Africa, I conclude that Peig is one of the most emotionally rich books in modern Irish. The article opens new ground in examining the question of class in Irish language literature, concluding that its universal themes continue to resonate in a contemporary multi-ethnic Ireland.